Interactions Between Insects and Certain Pest Control Factors in an Aquatic Ecosystem. I. Toxicity of Five Herbicides Used in Rice Fields to Different Stages of Culex pipiens L. - Abou-Bakr, Hassan; Helmi, Nahed; El Hussieni, Monir; Ramadan, Rawhia H. (Contributions to Entomology = Beiträge zur Entomologie, 1991)
Five herbecides commercially used for weed control in rice fields in Egypt were tested in the laboratory for their insecticidal activity against different stages of mosquito, Culex pipiens. Two compounds, i.e. Stromb 330 E and Rifit 550 EC demonstrated obvious larvicidal power when used at concentrations equivalent to field application rates. On theother hand, the other 3 compounds tested, i.e. Ordram, Machete and Ronstar did not affect mosquitoes when tested at normal rates.